1999
DOI: 10.1111/j.1151-2916.1999.tb01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Thermal Analysis on the Crystallization Kinetics of K2O‐B2O3‐MgO‐Al2O3‐SiO2‐TiO2‐F Glass

Abstract: The crystallization kinetics of a glass based on one type of mica, NaMg 3 AlSi 3 O 10 F 2 , with the addition of a nucleating agent, TiO 2 , has been studied using differential thermal analysis (DTA) under both isothermal and nonisothermal conditions. Two distinct crystallization exotherms in the DTA curve are observed and resolved that correspond to the initial formation of magnesium titanate (MgTi 2 O 5 ) and the later formation of mica. The activation energy for precipitation of each crystalline phase has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…3.3 kJ/mol, 144.3±9.2 kJ/mol and 176.3±12.5 kJ/mol, respectively, which are lower than the value obtained by Cheng [20] (275±6 kJ/mol). The discrepancy may attribute to the difference in the chemical compositions.…”
Section: Using the Following Modified Form Of Kissinger Equation Estacontrasting
confidence: 61%
“…3.3 kJ/mol, 144.3±9.2 kJ/mol and 176.3±12.5 kJ/mol, respectively, which are lower than the value obtained by Cheng [20] (275±6 kJ/mol). The discrepancy may attribute to the difference in the chemical compositions.…”
Section: Using the Following Modified Form Of Kissinger Equation Estacontrasting
confidence: 61%
“…On the other hand, the final stage of crystallization ( x >0.9) could be associated with the saturation of nucleation sites and the mutual contact of crystals. These might lead to the deviation of the plot of ln[−ln(1− x )] versus ln t from linearity 23 …”
Section: Resultsmentioning
confidence: 99%
“…The aim of this work is to explore the possibilities of SCTA, and in particular of CRTA, for the first time for studying kinetics of crystallization processes using the heat flow signal for monitoring the process, as an alternative to conventional linear heating or isothermal conditions . The potential of CRTA in crystallization studies is demonstrated by the analysis of the crystallization of a dried zirconia gel.…”
Section: Introductionmentioning
confidence: 98%